Penyediaan Infrastruktur dan Environmental Justice: Dampak Keberadaan Tempat Pembuangan Akhir Sampah bagi Masyarakat Sekitar - Sri Maryati (PLANNERS INSIGHT : URBAN AND REGIONAL PLANNING JOURNAL, 2019)
In the context of environmental justice (EJ) this paper explores the impact of providing solid waste infrastructure to the communities. Solid waste infrastructure that is beneficial to certain community groups has a negative impact on other community groups because it is not managed well. The research method used is a qualitative and quantitative analysis method. This research shows that the poor management of waste infrastructure in the past, currently still causes various impacts to the community. Some of the impacts are decreasing water quality, odor, decreasing environmental aesthetics, and decreasing land prices. Some implications and recommendations are proposed to overcome the EJ problem, including the provision of public clean water infrastructure, provision of buffer zones, shelter and leachate management, and strengthening guidelines for the determination of landfill sites located in two administrative areas or bordering other administrative areas, or landfill in one region that located in another administrative area.